HIV/AIDS care and treatment for people who inject drugs in Asia and the Pacific : an essential practice guide. (World Health Organization, Regional Office for South-East-Asia ; World Health Organization, Regional Office for the Western Pacific ; United Nations Office on Drugs and Crime, Regional Centre for East Asia and the Pacific, 2008)
This Guide is based on discussions with health care workers, researchers and program managers from South-East Asia and the Western Pacific Regions and the experiences from scaling-up ART and harm reduction services. The Guide is complementary to the global ART guidelines and considers the need of physicians, program planners, other health care workers, people living with HIV, and drug users to have one simplified user-friendly reference guide for the national adaptation on management of HIV infection and antiretroviral therapy for IDUs.